2014
DOI: 10.1002/elps.201300486
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex single nucleotide polymorphism genotyping method using ligase‐based mismatch discrimination and CE‐SSCP

Abstract: Accuracy, simplicity, and cost-effectiveness are the most important criteria for a genotyping method for SNPs compatible with clinical use. One method developed for SNP genotyping, ligase-based discrimination, is considered the simplest for clinical diagnosis. However, multiplex assays using this method are limited by the detection method. Although CE has been introduced as an alternative to error prone microarray-based detection, the design process and multiplex assay procedure are complicated because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The main drawback for fluorescent detection is photo-bleaching. Fluorescent detection has been successfully applied in multiplex detection of various SNPs and mutations using various fluorescent probes or the same fluorescent label but with different sized LCR amplicons [53,57].…”
Section: Fluorescent Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main drawback for fluorescent detection is photo-bleaching. Fluorescent detection has been successfully applied in multiplex detection of various SNPs and mutations using various fluorescent probes or the same fluorescent label but with different sized LCR amplicons [53,57].…”
Section: Fluorescent Methodsmentioning
confidence: 99%
“…This universal chip platform has also been microfabricated with polycarbonate and poly(methyl methacrylate) for the detection of K-ras oncogene SNPs [56]. Choi et al reported a multiplex SNP genotyping assay consisting of multiplex PCR pre-amplification, ligation with DNA ligase and CE-fSSCP to increase resolving power for similar sized probes [57]. This assay was able to accurately discriminate SNPs in the tp53 gene.…”
Section: Ligase Detection Reaction (Ldr)mentioning
confidence: 99%
See 3 more Smart Citations